Resistensi Buruh Anak Studi Resistensi Buruh Anak Dalam Hubungan Kerja Di Perkebunan Tembakau Ajung- Jember, Propinsi Jawa Timur - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Generally, this research tries to indentify and analyze causes, forms, and impacts of child labour working relation in tobacco plantation. Specifically, this research has some certain point of goals. First, to explain more detail about the working condition and eksploitation child labour in plantation sector. Second, to know and analyze the form of child labour resistence. That is hidden and open. Third, analyzing the impacts of hidden and open child labour resistence in the tobacco plantation. This research conducted in Tobacco Plantation PTPN X, that situated in Ajung-Jember, East Java. This study interviewed 100 responden to give the ilustration of child labour resistence. From 100 responden 15 of them were in depth interview to give qualitative data. This important field finding in this research is the double marginalized condition of the child. Firstly, that condition was formed by the structural pressure of their supervisor (mandor and mbok). Secondly, they also have unequal relation with senior labour that subordinate them. This child labour resistence caused by the unfair treatment like cutting wage, accept anger was frequently, and sexual harrasment problem committed by the mandor, mbok and senior labour. This kind of resistence is one of safest solution to them to maintain their work in the plantation. This finding was proved by the fact that denoting almost all of the child labour can avoid the negative impact from this kind of resistence. In the other hand, the changing situation above is the main willingness of the child labour but still not responded by the plantation management.